2019
DOI: 10.3390/toxins11020096
|View full text |Cite
|
Sign up to set email alerts
|

Chronic In Vivo Effects of Repeated Exposure to Low Oral Doses of Tetrodotoxin: Preliminary Evidence of Nephrotoxicity and Cardiotoxicity

Abstract: Tetrodotoxin (TTX) is one of the most potent naturally occurring neurotoxins. InitiallyTTX was associated with human food intoxications in Japan, but nowadays, concerns about thehuman health risks posed by TTX have increased in Europe after the identification of the toxin infish, marine gastropods, and bivalves captured in European waters. Even when TTX monitoring isnot currently performed in Europe, an acute oral no observable effect level (NOAEL) of 75 μg/kghas been recently established but, to date, no stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…An acute oral lethal dose 50 (LD 50 ) of 232 μg/kg TTX per body weight (BW), and a NOAEL of 75 μg/kg after monitoring the mice for two hours have been established [19] and adopted by the EFSA opinion, leading to the introduction of the establishment 44 μg TTX equivalents/kg shellfish meat as a safe concentration in fishery products, but until the time it was published there were no data available with regard to chronic or subchronic oral toxicity of TTXs, this being one of the recommendations of the relevant EFSA Panel for further data necessity [16]. In this context, a preliminary evaluation of the in vivo chronic effects of repeated exposure to low oral TTX doses (below the LD 50 ), following internationally adopted guidelines, was conducted by Boente-Juncal et al [18]. TTX was administrated daily to 4-week old Swiss female mice by gavage for a period of 28 days at doses ranging from 25 to 125 μg/kg.…”
Section: Hazard Identification and Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…An acute oral lethal dose 50 (LD 50 ) of 232 μg/kg TTX per body weight (BW), and a NOAEL of 75 μg/kg after monitoring the mice for two hours have been established [19] and adopted by the EFSA opinion, leading to the introduction of the establishment 44 μg TTX equivalents/kg shellfish meat as a safe concentration in fishery products, but until the time it was published there were no data available with regard to chronic or subchronic oral toxicity of TTXs, this being one of the recommendations of the relevant EFSA Panel for further data necessity [16]. In this context, a preliminary evaluation of the in vivo chronic effects of repeated exposure to low oral TTX doses (below the LD 50 ), following internationally adopted guidelines, was conducted by Boente-Juncal et al [18]. TTX was administrated daily to 4-week old Swiss female mice by gavage for a period of 28 days at doses ranging from 25 to 125 μg/kg.…”
Section: Hazard Identification and Characterisationmentioning
confidence: 99%
“…It was also shown that daily repeated exposure of mice to TTX at doses of 125 μg/kg led to ultrastructural changes in the kidney and myocardium. Despite the low number of mice surviving the whole 28-day experimentation at the higher TTX doses, these data constitute a useful initial approach to evaluate the potentially harmful effects after repeated in vivo oral exposure to TTXs [18].…”
Section: Hazard Identification and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood was obtained directly from the ventricle of euthanized mice as previously described [ 35 , 57 ] and conserved in microtubes containing lithium heparin (2.5 U.I./mL) until the end of the necropsy and tissue collection (30 min). Afterwards, each blood sample was mixed for 30 s and centrifugated for 90 s at 15,800 rpm/12,000× g (IDEXX Stat Spin, IDEXX Europe B.V., Hoofddorp, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Stomach samples preparation for transmission electron microscopy was performed according to previously described procedures [ 35 , 57 , 58 ]. Concisely, organ samples (1 mm 3 ) were fixed by immersion (2.5% glutaraldehyde in phosphate buffered saline (PBS) containing in mM: 137 NaCl, 8.2 Na 2 HPO 4 , 1.5 KH 2 PO 4 and 3.2 KCl) for 2 h at 4 °C and rinsed three times with PBS.…”
Section: Methodsmentioning
confidence: 99%